Dock3 protects myelin in the cuprizone model for demyelination - Namekata, K (Cell Death Dis, 2014)
Dedicator of cytokinesis 3 (Dock3) belongs to an atypical family of the guanine nucleotide exchange factors. It is predominantly expressed in the neural tissues and causes cellular morphological changes by activating the small GTPase Rac1. We previously reported that Dock3 overexpression protects retinal ganglion cells from excitotoxic cell death. Oligodendrocytes are the myelinating cells of axons in the central nervous system and these cells are damaged in demyelinating disorders including multiple sclerosis (MS) and optic neuritis. In this study, we examined if Dock3 is expressed in oligodendrocytes and if increasing Dock3 signals can suppress demyelination in a cuprizone-induced demyelination model, an animal model of MS. We demonstrate that Dock3 is expressed in oligodendrocytes and Dock3 overexpression protects myelin in the corpus callosum following cuprizone treatment. Furthermore, we show that cuprizone demyelinates optic nerves and the extent of demyelination is ameliorated in mice overexpressing Dock3. Cuprizone treatment impairs visual function, which was demonstrated by multifocal electroretinograms, an established non-invasive method, and Dock3 overexpression prevented this effect. In mice overexpressing Dock3, Erk activation is increased, suggesting this may at least partly explain the observed protective effects. Our findings suggest that Dock3 may be a therapeutic target for demyelinating disorders including optic neuritis.